Perjanjian Franchise Antara Mysalon Dan Ratnasari Lukitaningrum (Studi Putusan Mahkamah Agung No.493/Pdt/2018/Pt.DKI) - Shabriansyah, Rahmat Ivan; Tamrin, Abu (JOURNAL of LEGAL RESEARCH, 2025)
This study analyzes the breach of contract (wanprestatie) committed by a franchisee in executing the agreement established with the franchisor. The research adopts a statute approach combined with an analytical approach to examine the relevant legal provisions and their practical implications. The findings indicate that RL, as the franchisee, failed to fulfill contractual obligations under the agreement with MYSalon, the franchisor. Initially, MYSalon demonstrated good faith by summoning the franchisee and offering an opportunity to settle outstanding payment obligations. However, the franchisee refused to comply and instead unilaterally closed the MYSalon outlet under their management while filing a lawsuit before the South Jakarta District Court. To prevent the franchisor’s claim from becoming illusory and to ensure compensation for material losses, the franchisor requested the court to impose a conservatory attachment (conservatoir beslag) on all movable assets, equipment, and furniture owned by the franchisee across all managed outlets. Furthermore, the franchisor petitioned the court to prohibit the franchisee from using the MYSalon name and trademark, which legally belong to the franchisor.